Long-term Results after Hallux Valgus Correction with Distal Metatarsal Reversed-L (ReveL) Osteotomy: Which Factors Influence Recurrence and the Clinical Outcome? - Lizzy Weigelt MD; Noah Davolio; Carlos Torrez MD; Florian Haug MD; Nathalie Kühne; Stephan H. Wirth MD (Foot & Ankle Orthopaedics)
Category: Bunion; Midfoot/Forefoot Introduction/Purpose: The study objective was to evaluate the long-term results of hallux valgus correction with a distal metatarsal reversed-L (ReveL) osteotomy. Moreover, potential risk factors leading to recurrence and an inferior clinical outcome were assessed. Methods: Eighty-eight patients (131 feet) were evaluated after a mean follow-up of 14.2 (range, 10 – 18) years. Weightbearing foot radiographs were analyzed preoperatively, 6 weeks postoperatively, and at the final follow-up for the following parameters: hallux valgus angle (HVA), intermetatarsal angle (IMA), first metatarsophalangeal joint (MTPJ) congruence angle, sesamoid position, presence of round sign, first MTPJ arthritis. The Visual Analog Scale (VAS) and the Foot and Ankle Outcome Score (FAOS) assessed postoperative pain and function. Univariate and multivariate logistic regression analyses identified risk factors for hallux valgus recurrence and an inferior clinical outcome. Results: All radiographic parameters significantly improved at the 6-week and the final follow-up (p< 0.001). The recurrence rate (HVA ≥ 20°) was 13.7%. A preoperative HVA > 28° (OR 9.1; p= 0.02) and a 6-week postoperative HVA > 15° (OR 4.6; p= 0.03) were independent risk factors for recurrence. A preoperative BMI > 30 kg/m 2 correlated with lower FAOS quality of life (p= 0.04), and postoperative hallux varus with lower FAOS activities of daily living (p < 0.05). First MTPJ arthritis ≥ grade 2 at the final follow-up significantly correlated with lower FAOS subscales. Recurrence had no impact on the long-term outcome. Disturbing hardware was the main cause of revision (14.5%). 94% were satisfied with the hallux appearance and 92% with pain reduction. Conclusion: Hallux valgus correction with a ReveL osteotomy leads to high long-term satisfaction rates. A preoperative HVA >28° and a 6-week postoperative HVA >15° increased the risk for hallux valgus recurrence. First MTPJ arthritis was the leading cause for an inferior clinical long-term outcome. Radiographic hallux valgus recurrence had no impact on the clinical results.